The effects of voltage variations and surface on the performance of an HHO generator using a NaOH catalyst - Marullah Ridwan, Asmawi; Mansor, Muhd Ridzuan; Tamaldin, Noreffendy; Sudrajat, Ajat; Repi, Viktor Vekky Ronald; Latief, Fahamsyah Hamdan (Engineering and Applied Science Research, 2025)
The objective of this work is to test the HHO generator by implementing innovations on the electrode plate surface and varying the input voltage. Some important indicators, such as H2 gas production rate, output current, output temperature, and operating time, were carefully tested as an evaluation of the HHO generator’s performance. The HHO generator’s electrolyte was NaOH as a catalyst, and the concentration was maintained at 60 g/l. This study is mostly interested in how the voltage changed between 12V and 14V when different electrode surface textures were used. The findings demonstrated that an increase in voltage generally exhibits an increasing trend in H2 gas production rate, output current, and output temperature, along with a decrease in operating time. The most striking was the H2 production rate, which increased significantly by 422.13% with the voltage variations on the cross surface. Even the output current and output temperature were quite high on the cross surface as a function of voltage variation. In contrast, the operating time showed a sharp decrease with the increase in voltage on the cross surface, from 98.06 s at 12 V to 18.78 s at 14 V. It should be noted that the cross surface revealed the shortest operating time and was also the most efficient in the HHO gas production process compared to other types of surfaces. This research can aid in the addition of gas to improve the performance and emissions of gasoline engines.